Usage and Application Prospects QR Codes - Deineko, Zh.; Sotnik, S.; Lyashenko, V. (IJEAIS, 2022)
The paper considers 6 types of QR codes and real examples of their application, as a result, diagram visualizing the general statistics of the use of QR codes in 4 most promising areas is presented. This article is an overview of QR codes wit h their characteristics and versions. The article briefly presents applications for Android and devices for access control with ability to read barcodes, analyzing their functions and formats.
Keywords: QR code; reader